Menghidupkan Kembali Semangat Gotong Royong di Era Modern Agar Mengembalikan Nilai-Nilai Kebersamaan Untuk Menyatukan Masyarakat Indonesia - Mohamad Aren Gracia Shandy; Edy Soesanto; Ahmad Faizal (International Forum of Researchers and Lecturers, 2025)
Indonesia is known for its diversity of culture, ethnicity, religion and customs. One of the noble values ​​contained in Indonesian culture is the spirit of mutual cooperation. Mutual cooperation is a form of cooperation between individuals or groups in solving work or problems together, regardless of social status, background or personal interests. In the history of the Indonesian nation, this spirit has proven to be a solid foundation in building social solidarity, strengthening unity, and supporting the sustainability of social life. However, along with the times and rapid advances in technology, the value of mutual cooperation has begun to be replaced by the values ​​of more individualism. emphasizes personal interests and individual achievements. The modern era, with all the dynamics and influence of globalization, has caused many people to focus more on personal success without considering collective interests. This aims to re-explore the spirit of mutual cooperation in the modern era with an approach that is relevant to current developments, as well as finding ways to restore the value of togetherness which is increasingly being eroded by individualism.